Synthesis of Hierarchical Mesoporous ZIF-8 Functionalized with 1,2,4-Triazole by Mixed-Ligand Strategy for Enhanced CO2 Fixation Under Atmospheric Pressure - Thi Nguyen, Que; Bae, Yejin; Do, Xuan Huy; Kim, Sang Hoon; Na, Jongbeom; Baek, Kyung-Youl; Lee, Yu-Ri (American Chemical Society, 2024)
This work demonstrates the development of a hierarchical mesoporous hybrid ZIF-8 with 1,2,4-triazole (T), ZIF-8T, as a heterogeneous catalyst for CO2 cycloaddition to epoxides under a solvent- and cocatalyst-free conditions at ambient pressure. The hybrid ZIF-8T catalyst was prepared via a facile one-pot synthesis method using a mixed-ligand of 2-methyl imidazole (2-Mim) and T. The contents of the introduced T ligand in ZIF-8T were controlled by adjusting a molar ratio of T: 2-Mim ligand. Interestingly, the ZIF-8T with 84.9% of T contents showed a hierarchical hollow mesopore properties and it exhibited excellent catalytic performance with 100% conversion of epichlorohydrin with high selectivity (>99%) under mild conditions (80 degrees C, 1 bar CO2). In addition, ZIF-8T showed high catalytic activity toward various epoxide substrates. This significant activity of ZIF-8T was attributed to the synergistic effect of the abundance of Lewis acid/base sites derived from unsaturated Zn node and N species in T and 2-Mim ligand, along with the inherent properties of hierarchical mesoporosity. Various reaction parameters, including the effect of the reaction temperature, time, and catalyst loading, were investigated to optimize the reaction condition. Additionally, reaction kinetics and the reusability test of the ZIF-8T catalyst were conducted. Based on the results obtained, a plausible reaction mechanism for CO2-epoxide cycloaddition catalyzed by the ZIF-8T catalyst was also predicted.